Single-cell sequencing and its applications in head and neck cancer. (December 2019) - Qi, Zongtai; Barrett, Thomas; Parikh, Anuraag S.; Tirosh, Itay; Puram, Sidharth V.
Highlights: Head and neck squamous cell carcinoma (HNSCC) is characterized by significant intra -tumoral heterogeneity. Single-cell sequencing (SCS) technologies provide valuable insights into tumor heterogeneity. SCS reveals genetic, transcriptional, and epigenetic diversity among malignant, stromal, and immune cells. SCS is likely to alter the management of HNSCC as it improves diagnosis and facilitates novel therapeutic design. Advances in SCS should allow this technology to be integrated into clinical decision-making. Abstract: Head and neck squamous cell carcinoma (HNSCC), like many tumors, is characterized by significant intra -tumoral heterogeneity, namely transcriptional, genetic, and epigenetic differences that define distinct cellular subpopulations. While it has been established that intra -tumoral heterogeneity may have prognostic significance in HNSCC, we are only beginning to describe and define such heterogeneity at a cellular resolution. Recent advances in single-cell sequencing technologies have been critical in this regard, opening new avenues in our understanding of more nuanced tumor biology by identifying distinct cellular subpopulations, dissecting signaling within the tumor microenvironment, and characterizing cellular genomic mutations and copy number aberrations. The combined effect of these insights is likely to be robust and meaningful changes in existing diagnostic and treatment algorithms through the application of novel biomarkers as well as targeted therapeutics. Here, we review single-cell technological and computational advances at the genomic, transcriptomic, and epigenomic levels, and discuss their applications in cancer research and clinical practice, with a specific focus on HNSCC.